Dr. João Amorim - Amorim, João (DEEPPLANE™ surgeon registry, 2026)
Surgeon profile record for Dr. João Amorim, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
CC-BY-4.0 licensed; published by DEEPPLANE™
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil